How metabolism bridles cytotoxic CD8+ T cells through epigenetic modifications. Issue 5 (May 2021) - Van Acker, Heleen H.; Ma, Shixin; Scolaro, Tommaso; Kaech, Susan M.; Mazzone, Massimiliano
Abstract : In the direct competition for metabolic resources between cancer cells and tumor-infiltrating CD8 + T cells, the latter are bound to lose out. These effector lymphocytes are therefore rendered exhausted or dysfunctional. Emerging insights into the mechanisms of T cell unresponsiveness in the tumor microenvironment (TME) point towards epigenetic mechanisms as crucial regulatory factors. In this review, we discuss the effects of characteristic components of the TME, i.e. glucose/amino acid dearth with elevated levels of reactive oxygen species (ROS), on DNA methylation and histone modifications in CD8 + T cells. We then take a closer look at the translational potential of epigenetic interventions that aim to improve current immunotherapeutic strategies, including the adoptive transfer of T cell receptor (TCR) or chimeric antigen receptor (CAR) engineered T cells. Highlights: The tumor microenvironment forms a metabolic barrier against cytotoxic CD8 + T cells, thus hampering current immunotherapeutic strategies. It is increasingly recognized that epigenetics bridges cellular metabolism with gene expression. Tackling epigenetic modifications or cell metabolism to (i) target the epigenetic signature of (tumor-infiltrating) CD8 + T cells in vivo, or (ii) potentiate the ex vivo generation of antitumor T cell grafts for adoptive cell transfer, has gained much interest as a promising strategy to combat malignancy.